Composites of rutile TiO2 nanorods loaded on graphene oxide nanosheet with enhanced electrochemical performance. (20th February 2015) - Liu, Ruirui; Guo, Wenjun; Sun, Bin; Pang, Jinli; Pei, Meishan; Zhou, Guowei
Graphical abstract: Highlights: A two-phase self-assembly approach was utilized to prepare TiO2 nanorod/GO. TiO2 nanorods were uniformly loaded on the surface of GO nanosheets. The electrochemical performance of TiO2 nanorod/GO was studied systematically TiO2 nanorod/GO exhibit much higher C s and cycle stability than bare TiO2 TiO2 nanorod/GO composite with 4.00 wt.% GO showed the highest C s. Abstract: TiO2 nanorod/graphene oxide (TiO2 nanorod/GO) composites with different TiO2 /GO weight ratios were successfully prepared by self-assembly of GO and ready-made TiO2 nanorods under room temperature conditions. TiO2 nanorods were synthesized via the hydrothermal method, and GO was obtained via a modified Hummers method. X-ray diffraction, atomic force microscopy, and high-resolution transmission electron microscopy indicated that rutile TiO2 nanorods were loaded on the GO nanosheet without obvious aggregation. The electrochemical performance of the TiO2 nanorod/GO composites was confirmed by cyclic voltammetry, galvanostatic charge–discharge, and electrochemical impedance spectroscopy in 1 mol L −1 Na2 SO4 aqueous electrolyte. The ratio of TiO2 nanorods to GO in composite materials has significant influence on electrochemical performance of composite electrodes. TiO2 nanorod/GO composites with 4.00 wt.% GO have excellent electrochemical performance. The maximum specific capacitance of this composite electrode was 100 F g −1 at 5 mV s −1 scan rate. The TiO2 nanorod/GO composites also exhibited good electrochemical stability with a capacitance degradation of less than 20% over 3000 cycles. The electrochemical performance of the as-prepared nanocomposites could be enhanced by increasing chemical interactions between TiO2 and GO.